Association of reported sleep disturbances with objectively assessed mild cognitive impairment among adults in the United States - Chan Shen; Hao Wang; Arthur Nguimatsa Djiotsop; R. Constance Wiener; Mona Pathak; Sophie Mitra; Patricia A Findley; Usha Sambamoorthi (SAGE Open Medicine)
Background: Sleep is a multifaceted phenomenon influenced by both duration and quality. Various sleep disturbances have been associated with mild cognitive impairment, but the role of specific disturbances in mild cognitive impairment pathophysiology remains unclear. This study investigated the associations between distinct sleep disturbances and mild cognitive impairment in adults aged 50 and older using nationally representative data. Methods: Longitudinal data from the Health and Retirement Study were analyzed to explore the association between mild cognitive impairment and three types of sleep disturbances: trouble falling asleep, trouble waking up, and waking up too early. Logistic regression models estimated unadjusted (Model 1) and adjusted associations accounting for sex, race/ethnicity, age, social determinants of health (Model 2), general health (Model 3), depression (Model 4), and pain and physical activity (Model 5). Results: The study cohort included 8877 participants aged ⩾50 years in 2018 (baseline) who were followed up in 2020. Overall, 15.4% reported trouble falling asleep, 23.2% reported trouble waking up, and 12.8% reported waking up too early and being unable to fall back asleep most of the time. Among older adults, approximately 13.1% reported experiencing mild cognitive impairment; The prevalence of mild cognitive impairment was even higher in those who experienced sleep disturbances. The unadjusted odds ratio (uOR) for experiencing trouble falling asleep most of the time was 1.69 (95% CI: 1.42–2.03), for trouble waking up most of the time was 1.31 (95% CI: 1.10–1.57), and for waking up early most of the time was 1.88 (95% CI: 1.51–2.35). However, these positive associations attenuated depending on the covariate adjustment. Conclusions: Nearly one in seven adults had mild cognitive impairment. The relationship between sleep disturbances and mild cognitive impairment has been challenging to delineate. Our findings demonstrate a positive association between sleep disturbances and mild cognitive impairment, although these associations were sensitive to covariate adjustments. These findings suggest multifaceted pathways for reducing the risk of mild cognitive impairment.